Managing State Border in the Context of Migration Crisis in Europe: Lithuanian Case - Aurelija Pūraitė; Saulius Greičius; Danguolė Seniutienė (Montenegrin Journal of Economics)
The aim of this paper has been the achievement of the level of scientific knowledge on the subject of research in terms of establishment and analysis of economic effectiveness of state border governance in Lithuania in the context of increasing migration in European Union. The objective also has been to suggest the possible measures for improvement of state border management bearing in mind the migration perspectives. There is an unexpressed demand on migration (especially immigration) as an economic and social phenomenon to have some positive impact on the economy of target country. It’s nevertheless true, that from political point of view the migration trends are usually being associated with the economic, social, security challenges in target countries. European Union countries which are the external borders of EU face with even more specific obstacles – the effective management of borders and necessity to bare costs of controlling migration flows. Therefore the effective use of economic and financial measures managing state borders is of the utmost importance reaching common goals of public security, stability, respect for European values and rule of law. The paper contains results of the analysis of international, regional and national legal acts and the secondary analysis of statistical data of European Union agencies and international organizations. The financial data of operational activities of Lithuanian State Border Guard Service is analysed, aiming to reveal the correlation between the effective management of state border control and financial support of the state and EU institutions.